CLINICAL AND EPIDEMIOLOGICAL CHARACTERISTICS OF COVID -19 IN JAIPUR, INDIA DURING THE PANDEMIC - Buranchieva , A.; Buranchieva , A.; Mayank , Sh. (EurasianUnionScientists, 2020)
Until now, the problem of coronavirus infection remains pressing, and many issues of this pathology remain open and little studied. The article examines COVID-19 clinical and epidemiological characteristics in Jaipur, India.